Molecular weight determination of a newly synthesized guanidinylated disulfide-containing poly(amido amine) by gel permeation chromatography - Haonan Xing; Mei Lu; Lei Xian; Jinmin Zhang; Tianzhi Yang; Li Yang; Pingtian Ding (Elsevier, 2017)
A cationic gene delivery vector, guanidinylated disulfide-containing poly(amido amine) (CAR-CBA), was synthesized by Michael addition reaction between N,N'-cystaminebisacrylamide (CBA) and guanidine hydrochloride (CAR). Gel permeation chromatography (GPC) was used to evaluate the molecular weight of synthesized CAR-CBA. Polyethyleneimine (PEI) with molecular weight of 25 kDa was adopted as a reference, and polyethylene glycols (PEG) with different molecular weights were used to establish a standard curve for determining the molecular weight of CAR-CBA. The effects of two critical factors, namely columns and eluents, on the molecular weight measurement of CAR-CBA were investigated to optimize the GPC quantitative method. The results showed that Ultrahydrogel columns (120, 250) and HAc-NaAc (0.5 M, pH 4.5) buffer solution were the optimal column and GPC eluent, respectively. The molecular weight of the synthesized CAR-CBA was analyzed by the optimized GPC method and determined to be 24.66 kDa.